The Influence of Information Technology and Task Complexity on Employee Performance - Andira Fitriani (BJRM (Bongaya Journal of Research in Management), 2022)
: This review plans to decide the impact of data innovation and assignment intricacy on representative execution at the Makassar City Territorial Resource Monetary Administration Office. Information assortment in this review was led utilizing a poll with a purposive inspecting strategy. The populace in this review were 125 workers of BPKAD, with the example choice of this review were representatives of Makassar City BPKAD, adding up to 56 individuals. The information investigation procedure utilized different direct relapse examinations with the assistance of the SPSS program. Given the consequences of the review, it very well may be seen that data innovation has a positive and inconsequential impact with a worth of (0.285) < (0.05) on the Presentation of Provincial Resources Monetary Administration Office Representatives and Assignment Intricacy has a critical impact with a worth of (0.00) < (0.05) on Execution At Local Resource Monetary Administration Office. Just as data innovation and assignment intricacy all the while positively affect worker execution at the Provincial Resource Monetary Administration Office